English for Islamic Boarding House (Pesantren)–Based College Students: Revealing the English Language Needs - Lina, Lina (Mulya Literasi Publishing, 2023)
This study aimed to investigate the learners’ perspective of perceived needs on the English language course at pesantren - based college that is considered as English for Specific Purposes. The needs are categorized as target needs and learning needs. The subject of the study were 26 students of Islamic Education department and 19 Quranic Sciences department students, as well as the 2 lecturers from each department. The data were collected through two techniques; the survey questionnaires which were addressed to students and interview to the lecturers. The quantitative data were analyzed using descriptive statistics by computing the percentage of the responses. Research findings revealed the target needs by identifying the goal of the English course that is to facilitate learners to communicate in English both spoken and written; while the learning needs by identifying the inputs of practicing the four skills should be both authentic and not authentic in nature as well as should contain subjects related to religious materials and every day used texts. The presented texts should be learnt through various procedures and arranged from guided to free guided tasks.